The General Movement Assessment Helps Us to Identify Preterm Infants at Risk for Cognitive Dysfunction - Einspieler, Christa; Bos, Arend F.; Libertus, Melissa E.; Marschik, Peter B. (Frontiers in Psychology, 2016)
Apart from motor and behavioral dysfunctions, deficits in cognitive skills are among the well-documented sequelae of preterm birth. However, early identification of infants at risk for poor cognition is still a challenge, as no clear association between pathological findings based on neuroimaging scans and cognitive functions have been detected as yet. The Prechtl General Movement Assessment (GMA) has shown its merits for the evaluation of the integrity of the young nervous system. It is a reliable tool for identifying infants at risk for neuromotor deficits. Recent studies on preterm infants demonstrate that abnormal general movements also reflect impairments of brain areas involved in cognitive development. The aim of this systematic review was to discuss studies that included (i) the Prechtl GMA applied in preterm infants, and (ii) cognitive outcome measures in six data bases. Seven studies met the inclusion criteria and yielded the following results: (a) children born preterm with consistently abnormal general movements up to 8 weeks after term had lower intelligence quotients at school age than children with an early normalization of general movements; (b) from 3 to 5 months after term, several qualitative and quantitative aspects of the concurrent motor repertoire, including postural patterns, were predictive of intelligence at 7 to 10 years of age. These findings in 428 individuals born preterm suggest that normal general movements along with a normal motor repertoire during the first months after term are markers for normal cognitive development until at least age 10.